The Study of College Students Subjective Well-Being Experiencing Online Learning: Examining the Role of Emotional Regulation and Social Support - Bahirah, Arifatul; Imaroh, Tukhas Shilul (Westscience Press, 2025)
This study uses a quantitative approach that aims to examine the role of emotional regulation and social support on the subjective well-being of students experiencing online learning as the impact of the COVID-19 pandemic. The research subjects were obtained through purposive sampling and amounted to 271 college students in Indonesia, consisting of 87 men and 184 women. The data collection instruments used in this study were the emotional regulation scale, the social support scale, and the subjective well-being scale of students. The results of the multiple regression analysis test proved that emotional regulation and social support played a significant role (p = 0.00) in the subjective well-being of students (R = 0.679). The results showed that the higher the emotional regulation and social support contribute to the higher level of student’s subjective well-being. In this study, it was found that the emotional regulation giving effective contribution of 28,6% and social support contributing 17,5% to the college students subjective well-being.